Constitutionality of Furnishing Publicly Financed Transportation to Private and Parochial School Students in Missouri - Gerald Tockman (Washington University Law Quarterly, 1963)
It is the purpose of this article to set forth those matters which are relevant to consideration of the constitutional question involved in connection with furnishing publicly-financed transportation to private and parochial school students in order to delineate that area of controversy with which any intelligible opinion on this question must deal. The objective of this article is to present an unbiased analysis of the legal factors involved, giving neither succor to those who raise the specter of papal tyranny nor assuagement to those who asseverate the progressing “godlessness” of this country.
Keywords: Schools and school districts